“Implementación de un plan de educación ambiental para el manejo de residuos sólidos en la unidad educativa ciudad de Valencia, del cantón Valencia” - Becerrin Escobar, Saul Roberto (2022)
The purpose of this research project was to implement an environmental education plan for solid waste management in the Educational Unit. City Valencia. Whose main objective was to promote a learning plan on environmental education. The research was developed using various information collection tools, such as: surveys, conversations, observation and analysis of documents. With this, it is planned to structure the theoretical foundation and the